Editorial - Borja Antela (Karanos, 2018)
To launch a new journal is never an easy task. Given the wealth of digital journals on Antiquity available today, what is the point of creating another one? This question, along with many others, will have occurred to anyone who has ever entertained the notion of becoming a journal editor.